The Sacred Matrix: Reclaiming the Feminine Body as Ontological Vocation in Hebrew and Malagasy Cosmologies - Rafaramalala Dyna; Robijaona Rahelivololoniaina Baholy (Budapest International Research and Critics University, 2025)
This theological reflection embarks on a profound comparative exegesis, plumbing the depths of the female body's symbolic resonance within two disparate yet remarkably convergent sacred traditions: ancient Hebrew biblical anthropology and the Malagasy cosmovision. Employing a rigorous interdisciplinary methodology that weaves together exegesis, symbolic anthropology, linguistics, and contextual theology, this study illuminates how both traditions imbue the feminine form with rich layers of sacred, ontological, and relational meaning. Central to this exploration is the Hebrew term neqēvāh (נְקֵבָה), commonly rendered